Telomere length, oxidative and epigenetic changes in blood DNA of patients with exacerbated psoriasis vulgaris - Beranek, Martin; Borsky, Pavel; Fiala, Zdenek; Andrys, Ctirad; Hamakova, Kvetoslava; Chmelarova, Marcela; Kovarikova, Helena; Karas, Adam; Kremlacek, Jan; Palicka, Vladimir; Borska, Lenka (Anais brasileiros de dermatologia, 2023)
BACKGROUND: The pathogenesis of psoriasis vulgaris involves changes in DNA molecules, genomic instability, telomere attrition, and epigenetic alterations among them. These changes are also considered important mechanisms of aging in cells and tissues. OBJECTIVE: This study dealt with oxidation damage, telomere length and methylation status in DNA originating from peripheral blood of 41 psoriatic patients and 30 healthy controls. METHODS: Oxidative damage of serum DNA/RNA was determined immunochemically. Real-time PCR was used for the analysis of the telomere length. ELISA technique determined levels of 5-methylcytosine in blood cells' DNA. RESULTS: Oxidative damage of serum DNA/RNA was higher in patients than in controls (median, 3758 vs. 2286pg/mL, p<0.001). A higher length of telomeres per chromosome was found in patients whole-cell DNA than in controls (3.57 vs. 3.04 kilobases, p=0.011). A negative correlation of the length of telomeres with an age of the control subjects was revealed (Spearman's rho=-0.420, p=0.028). Insignificantly different levels of 5-methylcytosine in patients and controls were observed (33.20 vs. 23.35%, p=0.234). No influences of sex, smoking, BMI, PASI score, and metabolic syndrome on the methylation status were found. STUDY LIMITATIONS: i) A relatively small number of the participants, particularly for reliable subgroup analyses, ii) the Caucasian origin of the participants possibly influencing the results of the parameters determined, and iii) Telomerase activity was not directly measured in serum or blood cells. CONCLUSION: The study demonstrated increased levels of oxidized DNA/RNA molecules in the serum of patients with exacerbated psoriasis vulgaris. The results were minimally influenced by sex, the presence of metabolic syndrome, or cigarette smoking. In the psoriatic blood cells' DNA, the authors observed longer telomeres compared to healthy controls, particularly in females. Insignificantly higher global DNA methylation in psoriasis cases compared to the controls indicated marginal clinical importance of this epigenetic test performed in the blood cells' DNA.
Keywords: oxidační stres; Epigenomics; Oxidative stress; psoriáza; Methylation; epigeneze genetická; metabolický syndrom; Metabolic Syndrome; Blood; 5-Methylcytosine; lidé; Psoriasis; RNA; ženské pohlaví; 5-methylcytosin; telomery; Humans; DNA; Female; Oxidative Stress; Telomere; Epigenesis, Genetic